Achievement Motivation and its Relationship to Locus of Control among Nursing Faculty Students in Tishreen University - حمود, سلاف (Latakia University Journal -Medical Sciences Series, 2021)
Achievement motivation is one of the important aspects of the human motivation system, as it determines the extent of the individual’s pursuit and perseverance in order to achieve and attain success. The level of achievement motivation is affected by several factors, including the locus of control, which is the individual's belief about his abilities to control the events and situations he is exposed to. This research aimed to identify achievement motivation and locus of control's level and to determine the relationship between them among faculty nursing students in Tishreen University and identify the variance in achievement motivation and locus of control's level according to sex and educational year. 200 students who were selected from the all four academic years by available sampling. The achievement motivation scale, which was prepared by Tarek Al-masri (2020) has been used. Locus of control scale (1966) also has been used; this scale has been translated into Arabic by Alaa Al -den kafafi in 1982. The most important results are (78.5%) have high achievement motivation level, and (68%) have external locus of control. We have discovered a negative statistic relationship between achievement motivation and locus of control, where the level of achievement motivation increases when the level of external locus of control decrease. Also, it was found no statistically significant differences in achievement motivation and locus of control's level according to sex and educational year.